2019
DOI: 10.1021/acs.nanolett.9b04307
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Manipulation of Cell Membrane Curvature by Light-Driven Reshaping of Azopolymer

Abstract: Local curvatures on the cell membrane serve as signaling hubs that promote curvature-dependent protein interactions and modulate a variety of cellular processes including endocytosis, exocytosis, and the actin cytoskeleton. However, precisely controlling the location and the degree of membrane curvature in live cells has not been possible until recently, where studies show that nanofabricated vertical structures on a substrate can imprint their shapes on the cell membrane to induce well-defined curvatures in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 60 publications
(106 reference statements)
0
37
0
Order By: Relevance
“…In turn, the resulting modulation of local curvature serves to recruit curvature-sensing proteins and lipids, which may further stabilize or increase local curvature differences 2 5 . Recent experiments on cells subject to controlled deformation, have confirmed the primary role of spatial curvature for inducing actin polymerization and recruiting curvature sensitive proteins 6 , 7 .…”
Section: Introductionmentioning
confidence: 95%
“…In turn, the resulting modulation of local curvature serves to recruit curvature-sensing proteins and lipids, which may further stabilize or increase local curvature differences 2 5 . Recent experiments on cells subject to controlled deformation, have confirmed the primary role of spatial curvature for inducing actin polymerization and recruiting curvature sensitive proteins 6 , 7 .…”
Section: Introductionmentioning
confidence: 95%
“…As discussed in this review, many proteins and lipids involved in signaling and cytoskeleton-anchoring are sensitive to membrane curvature ( 129 , 130 , 156 , 157 , 187 189 ). Therefore, regions on particles with high positive or negative curvature might well result in phagosomal domains of protein/lipid interactions and signaling.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Nano-topography-based methods such as electron-beam (E-beam) lithography can be used to create nanostructures as small as 50–100 nm, which enables high membrane curvatures ( 188 190 ). These approaches can be used for studying a wide range of questions related to curvature-induced distribution of clathrin-dependent endocytic proteins ( 187 ), polymerization of F-actin ( 188 , 189 ) and nuclear membrane deformations affecting chromatin distribution and gene expression ( 190 ). Using this approach, it was found that nano-topographies of above 30 nm are sensed by macrophages and printed patterns above 71 nm in height induce higher endocytic activity ( 193 ).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Because DPL offers facile control of the morphology, it can be incorporated into many other fields. A recent study applied photoinduced reshaping of azopolymers in bioscience (Figure d) . Soft lithography was used to fabricate azopolymer pillar arrays, and it was found that the membrane curvatures of the cells were dynamically changed, in confined environments, by azobenzene nanostructures.…”
Section: Applications Of Azopolymer‐based Nilmentioning
confidence: 99%